Social class, social self-esteem, and conspicuous consumption. Issue 2 (February 2021) - Oh, Ga-Eun (Grace)
Abstract: Previous research has suggested the negative relationship between self-esteem and conspicuous consumption since conspicuous consumption is aimed to gain social recognition and signal status. However, it has not been much explored how this relationship holds depending on social classes. We propose subjective social class will moderate the relationship between social self-esteem and conspicuous consumption. We also hypothesize the mediating roles of social dominance orientation and life satisfaction in the proposed moderation effect. By conducting the survey with the American sample, we tested these predictions. In Study 1, we showed that the negative relationship between social self-esteem and conspicuous consumption appeared only among high subjective social class individuals. In Study 2, we replicated Study 1 and further demonstrated that social dominance orientation and life satisfaction respectively mediated the interactive effect of subjective social class and social self-esteem on conspicuous consumption. The results suggest that among individuals who perceive themselves to be in a high social class, a low level of social self-esteem is conducive to conspicuous consumption. The theoretical implications and limitations of the present investigation are discussed. Abstract : social class; conspicuous consumption; self-esteem; social self-esteem; social dominance orientation; life satisfaction.